Panorama : De l'art optique au cinétisme - Jouffroy, Alain; Parra-Aledo, Marie José; Dyck, Jacques; Domecq, Jean-Philippe; Baatsch, Henri-Alexis; Lebrun, Jean-Baptiste; Naggar, Carole; Lascault, Gilbert; Sergeant, Philippe; Clay, Julien; Mavrommatis, Emmanuel; Tronche, Anne; et al. (Paris : Cahiers, 1978)
Giacometti ; Michaux ; Kowalski ; Pommereulle ; Duchamp ; Wittgenstein ; Renau, Jose ; Titus-Carmel ; Schlosser ; Ipousteguy ; Herbin ; Albers ; Vasarely ; Morellet, Francois ; Agam ; Soto ; Calder ; Tinguely, Jean ; Cruz-Diez ; Bury, Pol ; Takis
Cahiers d'art + Chroniques du jour
Lithographies originales d' Agam
boek
Keywords: Agam